New multi-part collisional model of the main belt: The contribution to near-Earth asteroids - Zain, Patricio Salvador (2020)
Aims. We developed a six-part collisional evolution model of the main asteroid belt (MB) and used it to study the contribution of the different regions of the MB to the near-Earth asteroids (NEAs). Methods. We built a statistical code called ACDC that simulates the collisional evolution of the MB split into six regions (namely Inner, Middle, Pristine, Outer, Cybele and High-Inclination belts) according to the positions of the major resonances present there (ν6, 3:1J, 5:2J, 7:3J and 2:1J). We consider the Yarkovsky effect and the mentioned resonances as the main mechanism that removes asteroids from the different regions of the MB and delivers them to the NEA region. We calculated the evolution of the NEAs coming from the different source regions by considering the bodies delivered by the resonances and mean dynamical timescales in the NEA population. Results. Our model is in agreement with the major observational constraints associated with the MB, such as the size distributions of the different regions of the MB and the number of large asteroid families. It is also able to reproduce the observed NEAs with H < 16 and agrees with recent estimations for H < 20, but deviates for smaller sizes. We find that most sources make a significant contribution to the NEAs; however the Inner and Middle belts stand out as the most important source of NEAs followed by the Outer belt. The contributions of the Pristine and Cybele regions are minor. The High-Inclination belt is the source of only a fraction of the actual observed NEAs with high inclination, as there are dynamical processes in that region that enable asteroids to increase and decrease their inclinations.